Corporate Governance Country Assessment : Ghana - World Bank (Washington, DC, 2014)
This report assesses Ghana s corporate governance policy framework. It highlights recent improvements in corporate governance regulation, makes policy recommendations, and provides investors with a benchmark against which to measure corporate governance in Ghana. It is an update of the 2005 Corporate Governance ROSC. Good corporate governance enhances investor trust, helps to protects minority shareholders, and can encourage better decision making and improved relations with workers, creditors, and other stakeholders. Better investor protection can lower the cost of capital and encourage companies to list and raise funds through equity markets. Investor protection is also crucial to protect retirement savings as pension funds invest more in listed companies. Good corporate governance also helps to ensure that these companies operate more transparently and efficiently.